POLICY TO REDUCE UNDER TWO STUNTING IN EAST JAVA REGION, INDONESIA: WHO IS THE RIGHT TARGET? - Laksono, Agung Dwi; Muis, Early Wulandari; Wulandari, Ratna Dwi (Universitas Airlangga, 2024)
Introduction: Currently, 22% of children worldwide are stunted, and more than half live in Asia. Stunting in East Java is still high in several areas, which should have been prevented, given the relatively good resources. Aims: The study analyzes the policy targets for reducing stunting children in East Java. Methods: The study examined 4,541 children. The study analyzed nutritional status, residence, maternal (age, marriage, education, employment, socioeconomic, prenatal class), and child characteristics (age, gender, and early breastfeeding initiation (EIBF)). Results: Children in urban regions were likelier than those in rural regions to experience stunting. Stunted children were more prevalent among mothers of all ages compared to those <20. Lower education correlated with a greater likelihood of having stunted children. Stunted children were 2.410 times more prevalent among married mothers than divorced/widowed mothers (95%CI 2.292-2.534). Stunted infants were 1.062 times more prevalent among unemployed mothers compared to employed mothers (95%CI 1.050-1.075). All socioeconomic levels have a higher probability than the wealthiest to experience stunting. Mothers with prenatal classes were 1.088 times more likely than those without to have stunted kids (95%CI 1.073-1.103). Children aged 12-23 had a greater likelihood of developing stunting than those younger than <12. Boys were 1.286 times more likely than girls to experience stunting (95%CI 1.272-1.300). Children with EIBF had a 1.081 times higher likelihood of experiencing stunting than those without (95%CI 1.069-1.093). Conclusion: The appropriate policy targets for reducing the stunting prevalence were mothers in urban areas, young age, married, poor educated, unemployed, and poor.